SMU launches GROW to kickstart a green movement - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
Ushering in the brand-new year with a fresh initiative GROW that sprouted today, SMU goes back to basics, advocating that transformative education begins with ‘U’ sowing the seeds and taking grounded steps to make a difference – in building a green and sustainable community for tomorrow. Officiating the launch, SMU President Professor Arnoud De Meyer and Mayor for Central Singapore District Denise Phua, joined hands in sharing the seeds of inspiration, planting the initiative firmly in the ground, and imparting the vision of SMU GROW. Also gracing the launch were partners from the Bras Basah Residents Committee, Edible Gardens, Potato Productions, and Nicole’s Café by Sterling.